Um estudo sobre remuneração variável de executivos em empresa de capital fechado - Marquezan, Luiz Henrique Figueira (Universidade do Vale do Rio dos Sinos, 2012)
The separation of ownership and control in companies originating the call agency relationship, in which shareholders (principal) delegate decisions to empower executives hired (agent). The Agency Theory, which studies this phenomenon has as one of their self-interest of those assumptions. Thus, one of the goals of management control is to ensure or reduce any differences between the interests of owners and executives. Theory indicates that the granting of incentives such as variable pay, for this purpose. In this context, this study aimed to study this phenomenon, about how a variable compensation system for executives used as a form of management control. To this end we carried out a survey applied to the reality of a company, which operates in the beverage industry, and has variable remuneration plans for performance. The procedures for collection of evidence were: direct observation, document analysis and semistructured interviews with ten executives included in these plans. The treatment of these occurred through the combination of the techniques of content analysis and discourse. Among other results, the evidence indicates that the company rewards performance with variable pay for bonuses and cash bonuses. These forms of reward, the times of payment at the end of each year, the use of financial performance indicators, and the pattern of annual performance, combined, can create an agency problem by directing the focus of executives to the short term. Offsetting this, there was the use of a way to evaluate the process of professional development executive in a qualitative manner, with effects of short and long term. The composition of three plans pay for performance provides alignment of interests: (a) between executives and other employees, (b) between the executive, to be paid by targets that do not show differences by using mathematical and collective goals and organizational; (c) between these members and executives with the greatest possibility of variable compensation tied to the achievement of the ultimate goal for the company, the EBITDA. As for interests, executives who are members demonstrate tranquility about the risk of this type of compensation, showing more concern about the continuity of the company's long-term. It was also the desire to own goals and challenges and professional development were identified as reasons for preferring executive incentive compensation. In addition to the compensation plans, the presence of two members among executives indicates a reduction of information asymmetry and greater ease in aligning the interests of both.
Keywords: Remuneração de executivos; Sistemas de recompensa; Conflitos de interesse; Teoria de agência; Executive compensation; Reward systems; Conflicts of interest; Agency theory; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis